Report on the status of women in the Turks and Caicos Islands (National Women in Development Committee [S.l.]TC, 1994)
Reviews and appraises at the national level the situation in the early eighties and changes since that time. Reviews amd appraises international support. Looks at future strategic goals and objectives and coresponding financial arrangements.
Prepared for th Fourth UN world Conference on Women, Beijing 1995